JIS Definition Identified More Malaysian Adults with Metabolic Syndrome Compared to the NCEP-ATP III and IDF Criteria. (23rd September 2013) - Ramli, Anis Safura; Daher, Aqil Mohammad; Noor Khan Nor-Ashikin, Mohamed; Mat-Nasir, Nafiza; Keat Ng, Kien; Miskan, Maizatullifah; Ambigga, Krishnapillai S.; Ariffin, Farnaza; Yasin Mazapuspavina, Md; Abdul-Razak, Suraya; Abdul-Hamid, Hasidah; Abd-Majid, Fadhlina; et al.
Abstract : Metabolic syndrome (MetS) is a steering force for the cardiovascular diseases epidemic in Asia. This study aimed to compare the prevalence of MetS in Malaysian adults using NCEP-ATP III, IDF, and JIS definitions, identify the demographic factors associated with MetS, and determine the level of agreement between these definitions. The analytic sample consisted of 8, 836 adults aged ≥30 years recruited at baseline in 2007–2011 from the Cardiovascular Risk Prevention Study (CRisPS), an ongoing, prospective cohort study involving 18 urban and 22 rural communities in Malaysia. JIS definition gave the highest overall prevalence (43.4%) compared to NCEP-ATP III (26.5%) and IDF (37.4%), P < 0.001 . Indians had significantly higher age-adjusted prevalence compared to other ethnic groups across all MetS definitions (30.1% by NCEP-ATP III, 50.8% by IDF, and 56.5% by JIS). The likelihood of having MetS amongst the rural and urban populations was similar across all definitions. A high level of agreement between the IDF and JIS was observed (Kappa index = 0.867), while there was a lower level of agreement between the IDF and NCEP-ATP III (Kappa index = 0.580). JIS definition identified more Malaysian adults with MetS and therefore should be recommended as the preferred diagnostic criterion.